KOSAKATA KEPADIAN DALAM BAHASA DAYAK BAKATIK DIALEK PALAYO - Arneka Arneka; Hotma Simanjuntak; Agus Syahrani (Universitas Tanjungpura, 2019)
AbstractThis study focused on observation to the rice farming of Dayak Bakatik dialect Palayo language. Rice farming activity of Dayak Bakatik Palayo community is one of livelihood that still maintained until nowadays. The reseaercher used qualitative research. Methods and research descriptive form. Technigues conducted by researcher in data collection is speech, fishing, face to face speech technique, note technique, and record technique. Tools data collection used in this research are interview, instrument, stationery, tape recorder, and camera. Based on the study conducted, the research has managet to collect 118 vocabulary. Overall the data consists of 10 classification, that is based on part of rice plant consists of 13 vocabulary, based on tools and material consist of 37 vocabulary, based on process consist of 25 vocabulary, based on ritual consists of 4 vocabulary, based on rice type consists of 7 vocabulary, based on land type of 4 vocabulary, based on type of weeds consists of 6 vocabulary, based on pests type consists of 10 vocabulary, based on processing the rice consists of 10 vocabulary, and based on myth consists of 2 vocabulary. Lexical meaning consist 92 vocabulary and cultural meaning consist 13 vocabulary.Keywords: Vocabulary, Rice Farming, Dayak Bakatik Palayo